Analisis Dan Perancangan Sistem Informasi Weighing Scale Truck Digital Menggunakan Metode OOAD - Moh. Kifliyanto; Mochammad Faid; Widjianto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Technology and information development are accelerating, and all operations currently make use of highly advanced technology. Likewise with the development of the construction sector such as industry and trade. One of them is a business involved in the distribution and transportation of goods. A business called CV. Anugrah is involved in the distribution and delivery of goods. The practice of weighing a load is one of the most crucial steps in the process of shipping products via truck. using the UML (Unified Modeling Language) and the Figma program to create a digital truck scale information system. Website design is made simpler with the aid of Figma. This project aims to develop a framework and design for a digital truck scale application that would make it simpler for administrators to weigh and record trucks. This architecture may make it simpler for programmers to create an application for an accurate digital truck scale. This study's methodology is qualitative. Use case diagrams, class diagrams, activity diagrams, sequence diagrams, a MySQL database, and the Figma application are used in the design of a digital weighing scale truck information system. The successfully created research findings are anticipated to be able to help the admin with the weighing process to make it simpler, faster, and more accurate